Mencermati Musik Kontemporer Kristen Sebagai Musik Ibadah Sebuah Tinjauan Musikologis - Daniel Sema (Sekolah Tinggi Teologi Jemaat Kristus Indonesia, Salatiga, 2022)
Today, in church worship occur hustle and bustle about the use of contemporary Christian music in worship. Proponents argue that God reigns over the praise, so any music is feasible in the presence of God; opponents consider that Christian contemporary music is less feasible because it was born as an alternative form of popular music and its relation to commercialism. In the middle of this clash of two groups, the development of contemporary Christian music increasingly unstoppable and continues to spread to fellowship and churches. This phenomenon is interesting because although underestimated by most people the Christian contemporary music is able to attract attention and liked by many people, especially young people.